2004
DOI: 10.1108/01437730410521831
|View full text |Cite
|
Sign up to set email alerts
|

The influence of organizational culture on attitudes toward organizational change

Abstract: This study investigates the influence of organizational culture on attitudes toward

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
48
0
4

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 178 publications
(53 citation statements)
references
References 31 publications
1
48
0
4
Order By: Relevance
“…This is highly problematic, as research clearly emphasises peoplerelated issues to be the primary reason for the failure of organisational change efforts (Atkinson, 2005;Cartwright & Cooper, 1994;Chawla & Kelloway, 2004;Karp, 2004; Roxburgh, 2003;Smith, 2005a;2005b;Rashid, Sambasivan & Rahman, 2004;Vakola et al, 2004;Worrall & Cooper, 2004). Aggravating this problem even further, is the fact that existing research on the people aspects of organisational change has to some extent also neglected a focus on the micro-level of organisational change (Vakola et al, 2004, p. 88) − that is, the individual − who is the focus of logotherapy.…”
Section: Rationale or Value-add Of The Studymentioning
confidence: 98%
“…This is highly problematic, as research clearly emphasises peoplerelated issues to be the primary reason for the failure of organisational change efforts (Atkinson, 2005;Cartwright & Cooper, 1994;Chawla & Kelloway, 2004;Karp, 2004; Roxburgh, 2003;Smith, 2005a;2005b;Rashid, Sambasivan & Rahman, 2004;Vakola et al, 2004;Worrall & Cooper, 2004). Aggravating this problem even further, is the fact that existing research on the people aspects of organisational change has to some extent also neglected a focus on the micro-level of organisational change (Vakola et al, 2004, p. 88) − that is, the individual − who is the focus of logotherapy.…”
Section: Rationale or Value-add Of The Studymentioning
confidence: 98%
“…This finding is in accordance with previous results suggesting that implementing new methods, models or practices in mental healthcare or healthcare is typically difficult [15,[22][23][24][25] . According to Rashid et al, it is important to understand the organizational culture before initiating projects towards change [57] . The cultural characteristics identified prior to the implementation process indicated that Ward 1, 2 and 4 were characterized by flexibility, cohesion and belongingness -a cultural profile that is beneficial to implementation processes, according to Carlström and Ekman [58] .…”
Section: Discussionmentioning
confidence: 99%
“…The resistance to change are sometimes enveloped in the "dealignment" between the organizational objectives and those of the employee, the outlook of the employee and his/her perception of the foci of the institution and the role(s) he plays in that position, and resistance to change owing to personality traits. In addition to the individualized culture of the people in the organization, there is a different organizational culture that is formed in institutions that play a key role to the change process (Pool, 2000;Ahmed, 1998;Silvester & Anderson, 1999;Rashid et al, 2003). Yukl outlines that in understanding the change process one should examine some of the theories such as Lewin's force-filed model.…”
Section: Changementioning
confidence: 99%